Dynamic fracture width prediction for lost circulation control and formation damage prevention in ultra-deep fractured tight reservoir. (1st January 2022) - Xu, Chengyuan; Yang, Xinglin; Liu, Chuan; Kang, Yili; Bai, Yingrui; You, Zhenjiang
Abstract: Dynamic fracture width prediction is of great importance to the control of lost circulation, which often leads to safety, environmental and economic issues and results in severe formation damage during the development of ultra-deep fractured tight reservoir. However, the connected fault boundary and nonlinear deformation behavior are rarely considered for the fracture width prediction. In the current paper, the fracture deformation equation is determined by fitting the stress sensitivity experiments data. The prediction model for dynamic fracture width is developed based on the non-Newtonian fluid loss dynamics theory, accounting for the power-law fluid, fracture index deformation equation and fault boundary. Parametrical analysis is conducted to investigate the effects of pressure difference, consistency coefficient, flow pattern index and fault boundary distance on the dynamic fracture width. Control strategy is proposed for drilling fluid loss in fractures with connected fault in ultra-deep fractured reservoir. The developed dynamic fracture width prediction model is validated by field data and successfully applied to the SHB ultra-deep fractured tight reservoir in Tarim Basin, China.